2006
DOI: 10.1596/1813-9450-3831
|View full text |Cite
|
Sign up to set email alerts
|

Exploring The Linkages Between Poverty, Marine Protected Area Management, And The Use Of Destructive Fishing Gear In Tanzania

Abstract: Coastal resources in Tanzania have come under increasing pressure over the past three decades, which has led to a significant decline in the biodiversity and productivity of coastal ecosystems. The livelihoods of coastal communities that directly depend on these resources are consequently under increasing threat and vulnerability. Marine Protected Areas (MPAs) are one tool for managing coastal and marine resources that have been increasingly used in Tanzania. Promotion of alternative income generating activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 21 publications
4
34
0
Order By: Relevance
“…Overall, the view taken of human wellbeing by the studies was limited. Only one study examined the full breadth of aspects (Silva 2006), while the vast majority examined only a small number. A narrow view of wellbeing is unlikely to reflect reality as improvements in measured aspects could be offset by undetected declines in others.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the view taken of human wellbeing by the studies was limited. Only one study examined the full breadth of aspects (Silva 2006), while the vast majority examined only a small number. A narrow view of wellbeing is unlikely to reflect reality as improvements in measured aspects could be offset by undetected declines in others.…”
Section: Discussionmentioning
confidence: 99%
“…Micro-level contextual factors that can influence outcomes include assets (i.e., natural, social, financial, physical, political, and human capital), underlying norms and values, pre-existing social and political structures, cultural practices, ecosystem health and population dynamics, resources utilized, and fishing methods or harvesting practices. The underlying assets in a community might be a particularly important focus for designing MPA-related development interventions as assets form the basis of livelihood options and adaptability, the choice of livelihoods, cultural norms, strength of institutions, levels of compliance, and choices of gear/use of destructive gear [91,105]. The localized biology and ecology of an area will also influence the level of fisheries or tourism benefits that are achievable from MPA creation [106].…”
Section: A Note On Context: Micro To Macro Considerationsmentioning
confidence: 99%
“…Consideration needs to be given to mitigating the social impacts of MPAs through enhancement and diversification of livelihoods [18,32,72,105]. This section explores the processes and inputs required to achieve more successful livelihood interventions.…”
Section: Development: Alternative Livelihoods and Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have found that fishers who are more educated or wealthier are more likely to use less destructive gear [14]; whereas those with female heads of households or suffering food insecurity use more destructive gear [3,14]. Some studies have determined that fishing strategies, including fishing ground selection and effort, depend on wealth and experience, as well as distance to the market, seasonal dynamics, traditions, profits and information [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%